An Analysis of Procedural and Conceptual Knowledge in Genetic Engineering Topic among STEM Students: Basis for Instructional Material Development - Anwar I. Kolong; Melbert C. Sepe (Bioeduca : Journal of Biology Education, 2025)
The objective of this study is to examine the levels of procedural and conceptual knowledge in genetic engineering topics among STEM students to provide baseline in developing effective instructional materials. Topics such as introduction to Genetic engineering, Gene Cloning, and DNA extraction were utilized to determine levels of students’types of knowledge, procedural and Conceptual. A descriptive quantitative research approach using 12-item test is used to analyze and assess both procedural and conceptual knowledge using a 5-point Likert scale was used to measure students’ understanding. A total of 12 STEM students from Concepcion National High School took part in the study during the 2023-2024 academic year. The findings of the study revealed that students demonstrated higher levels of proficiency in procedural knowledge compared to conceptual knowledge across the three topics: genetic engineering, gene cloning, and DNA extraction. There appears to be a range of understanding levels when it comes to procedural knowledge, as indicated by the higher variability. On the other hand, the lower variability in DNA extraction suggests a more consistent level of comprehension. The study's small sample size limited the use of inferential statistical methods, highlighting the importance of finding more effective teaching methods to improve students' comprehension of genetic engineering concepts. Qualitative data uncovered notable obstacles, including a dearth of interactive experiences and materials, underscoring the importance of active involvement and sufficient resources. Suggestions involve improving laboratory sessions, ensuring the availability of required materials, and implementing interactive teaching techniques to enhance students' understanding of genetic engineering. This study highlights the significance of well-rounded educational interventions to enhance both theoretical and practical knowledge in genetic engineering.